PENGARUH AKTIVITAS PUSAT PENELITIAN ILMU PENGETAHUAN DAN TEKNOLOGI DI TANGERANG SELATAN SEBAGAI TEMPAT PUSAT - Fika Harningtyas; Agung Sugiri (TATALOKA, 2019)
Research Centre for Science and Technology covers an area of 460 Ha located in South Tangerang, functions as a central place and interacts with influenced regions due to the need for industrialization and commercialization of research results. This is relates with Central Place Theory that’s spatial relations and its spreading arise as a natural consequence of market interactions that include small-scale economy with various forms of output. This study aims to determine how vast the spatial interaction of Puspiptek’s activities, by using descriptive quantitative method. Analytical techniques that used are descriptive analysis, Likert scoring, Klee weighting and spatial analysis. Indicators for backward linkage: (1)labor, (2)infrastructure, (3)support cooperation, and (4)investment then for forward linkage: (1)patents, (2)scientific publications, (3)scientific activities, (4)commercial cooperation and (5)profit. Backward and forward linkage then describe Puspiptek’s hierarchical condition. The result is spatial interaction Puspiptek in the national scope, supported by backward linkage is 54% of the labor domiciled from various regions in Indonesia and forward linkage into the national class category with a score of 770 from the range 547 - 1.001. The result can be a recommendation for some authorities as a consideration in the preparation of spatial plans framework to realize the proposed of Puspiptek as a National Strategic Area.